In league with Sherlock Holmes : stories inspired by the Sherlock Holmes canon - Corbett, David, 1953-; Edwards, Martin, 1955-; Gerritsen, Tess; Haas, Derek, 1970-; Hill, Joe; Hirahara, Naomi, 1962-; Morton, Lisa, 1958-; Parks, Brad, 1974-; Quartey, Kwei; Yarbro, Chelsea Quinn, 1942-; Ziskin, James W., 1960- (Pegasus Crime, 2020)
"The latest entry in Laurie R. King and Leslie S. Klinger's popular Sherlock Holmes-inspired mystery series, featuring fifteen talented authors and a multitude of new cases for Arthur Conan Doyle's most acclaimed detective. Sherlock Holmes has not only captivated readers for more than a century and a quarter, he has fascinated writers as well. Almost immediately, the detective's genius, mastery, and heroism became the standard by which other creators measured their creations, and the friendship between Holmes and Dr. Watson served as a brilliant model for those who followed Doyle. Not only did the Holmes tales influence the mystery genre but also tales of science-fiction, adventure, and the supernatural. It is little wonder, then, that when the renowned Sherlockians Laurie R. King and Leslie S. Klinger invited their writer-friends and colleagues to be inspired by the Holmes canon, a cornucopia of stories sprang forth, with more than sixty of the greatest modern writers participating in four acclaimed anthologies. Now, King and Klinger have invited another fifteen masters to become In League with Sherlock Holmes. The contributors to the pair's next volume, due out in December 2020, include award-winning authors of horror, thrillers, mysteries, westerns, and science-fiction, all bound together in admiration and affection for the original stories. Past tales have spanned the Victorian era, World War I, World War II, the post-war era, and contemporary America and England. They have featured familiar figures from literature and history, children, master sleuths, official police, unassuming amateurs, unlikely protagonists, even ghosts and robots. Some were new tales about Holmes and Watson; others were about people from Holmes's world or admirers of Holmes and his methods. The resulting stories are funny, haunting, thrilling, and surprising. All are unforgettable. The new collection promises more of the same!"--Provided by publisher.